Patient demographics, clinical characteristics and genetic mutations of DMD and BMD patients in Qatar Epidemiological and genetic profile of Duchenne muscular dystrophy and Becker muscular dystrophy patients in Qatar: a retrospective cohort study - Sawahreh, Mohammad; Al-Maadid, Fatima; Ibrahim, Khalid Omer; Omran, Tawfeg Ben; Osman, Mahmoud Fawzi (Frontiers in Pediatrics, 2025)
BackgroundDuchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are rare X-linked neuromuscular disorders that typically begin in childhood and progress to functional decline, loss of ambulation, and early death due to cardiac or respiratory failure.ObjectiveTo describe the landscape of DMD and BMD in Qatar, including demographics, genetics, disease progression, risk factors, co-morbidities, and outcomes in patients aged 3–30 years, and compare findings with international data.MethodsWe retrospectively reviewed records of all genetically confirmed or biopsy-supported cases of DMD and BMD between 2018 and 2024 at Sidra Medicine, the sole pediatric tertiary center in Qatar.ResultsOf the 37 symptomatic patients (36 DMD, 1 BMD), 36 were male and one was a symptomatic female. The mean age was 18 years (range 3–30). At diagnosis, median age was 3.0 years. Twenty-two (59%) had orthopedic complications (scoliosis, contractures), 9 (24%) could still run, and 12 (32%) could climb stairs. Corticosteroids were prescribed in 14 patients (38%), most commonly deflazacort and prednisone. Cardiac medications were started in 7 patients (19%) around age 10. CK was elevated in 36/37 (range: 2,300–45,000 U/L). Epilepsy was documented in 3 patients; 3 had autism and 1 had ADHD. Genetic mutations included deletions (69%), duplications (11%), and point mutations (19%). Seven patients had mutations affecting Dp140/Dp71 isoforms and cognitive impairment.ConclusionsOur cohort reveals earlier diagnosis but lower life expectancy compared to international standards, likely due to lower corticosteroid and cardioprotective use. The findings support the need for strengthened multidisciplinary and early genetic-based interventions in Qatar